Quantitative Estimation of Gallic Acid From Hydroalcoholic Extract of Dried Flowers of Nymphaea stellata, Willd by RP-HPLC - Uttam Rakesh, Sachin; R. Patil, Priyanka; Salunkhe, V.R.; Dhabale, P.N.; Burade, K.B.; Bhise, S.B. (Asian Journal of Chemistry, 2010)
Several polyphenols have been tested in Nymphaea stellata, Willd. The flavonoid content is important because of the pharmacological properties of these compounds, whereas quercetin has been proved to be an antioxidant, antiinflammatory and hepatoprotective compound. A reversed-phase HPLC method has been developed and applied to determine quercetin content in hydroalcoholic extract of dried flowers of Nymphaea stellata in a single analysis. The gallic acid was analyzed with a HiQ Sil C-18 column by isocratic elution using 0.01 % (v/v) orthophosphoric acid:acetonitrile (95:5 v/v) as the mobile phase. The flow rate was 1.2 mL min-1 and detection was set at 265 nm. The recovery of the method was in the range of 98.50-99.40 % and all the compounds showed good linearity (r = 0.98332) in a relatively wide concentration range.